An oxidation and ring contraction approach to the synthesis of (+/-)-1-deoxynojirimycin and (+/-)-1-deoxyaltronojirimycin. - Bagal, S; Davies, S; Lee, J; Roberts, P; Russell, A; Scott, P; Thomson, J (2010)
A reaction sequence involving the chemoselective olefinic oxidation of N(1)-benzyl-2,7-dihydro-1H-azepine with m-CPBA in the presence of HBF(4) and BnOH followed by ring contraction facilitates the stereoselective preparation of either of the epoxide diastereoisomers of (2RS,3SR)-N(1)-benzyl-2-chloromethyl-3-benzyloxy-4,5-epoxypiperidine by simple modification of the reaction conditions. Epoxide ring opening, functional group interconversion, and deprotection allow the synthesis of (+/-)-1-deoxynojirimycin and (+/-)-1-deoxyaltronojirimycin.